A route to continuous ultra-thin cerium oxide films on Cu(111) - Staudt, T.; Lykhach, Yaroslava; Hammer, Lutz; Schneider, M. Alexander; Matolin, Vladimir; Libuda, Jörg (Surface Science, 2009)
The growth and morphology of ultra-thin CeO(2) (1 1 1) films on a Cu(1 1 1) substrate were investigated by means of low energy electron diffraction (LEED) and scanning tunneling microscopy (STM). The films were grown by physical vapor deposition of cerium in an oxygen atmosphere at different sample temperatures. The preparation procedure is based on a modification of a previous method suggested by Matolin and co-workers [1], involving growth at elevated temperature (520 K). Here, LEED shows good long range ordering with a "(1.5 x 1.5)" superstructure, but STM reveals a three-dimensional growth mode (Vollmer-Weber) with formation of a closed film only at larger thickness. Using a kinetically limited growth process by reactive deposition at low sample temperatures (100 K) and subsequent annealing, we show that closed layers of ceria with atomically flat terraces can be prepared even in the regime of ultra-thin films (1.5 ML). Closed and atomically flat ceria films of larger thickness (3 ML) are obtained by applying a multistep preparation procedure, in which successive ceria layers are homoepitaxially grown on this initial film. The resulting overlayers show strong similarities with the morphology of CeO(2)(1 1 1) single crystal surfaces, suggesting the possibility to model bulk ceria by thin film systems. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: Ceria; Ultra-thin oxide films; Scanning tunneling microscopy; Low energy electron diffraction; Model catalysts